2021
DOI: 10.1108/sasbe-10-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of cost misperceptions obstructing the adoption of sustainable buildings

Abstract: PurposeAcross the globe, the dearth of certainty about the cost of sustainable buildings (SBs) remains a critical disincentive to their adoption. This study explored the factually incorrect knowledge about the cost of SBs and their implications on adoption.Design/methodology/approachThe study adopted sequenced mixed qualitative and quantitative approaches involving a literature review, Delphi study and survey. Semi-structured and structured self-study questionnaires were administered to a random sample of gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Critical stakeholders also have the responsibility to disseminate this knowledge across educational segments, industry, public and practice to quicken the transfer of this knowledge to project implementation. Ekung et al (2021) posited that improved education and awareness are objective to entrench suitable cost perception needed by stakeholders during sustainable design adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Critical stakeholders also have the responsibility to disseminate this knowledge across educational segments, industry, public and practice to quicken the transfer of this knowledge to project implementation. Ekung et al (2021) posited that improved education and awareness are objective to entrench suitable cost perception needed by stakeholders during sustainable design adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha Cronbach reliability test was performed to determine the consistency of respondents' views about the significant problems caused by the COVID-19 pandemic in the construction industry. The Cronbach test is valid at a value greater than 0.70 (Ekung et al, 2022). The measurement constructs and variables in the study showed strong internal coherency with a Cronbach alpha value (0.823 > 0.70); therefore, the inter-item consistency and instrument reliability are deemed significant (0.823>0.70).…”
Section: Discussionmentioning
confidence: 77%
“…Construction professionals were deemed suitable for the study based on the direct impact of COVID-19 problems on their operations as well as their organisations. Ekung, Odesola, and Oladokun (2022) reported that quantity surveying consultancy outfits in the region have witnessed declined commissions since early 2020; therefore, professionals in this category are a veritable source of data for uncovering the problems caused by the COVID-19 pandemic. Studies have also portrayed the knowledge of construction professionals as a rich repository of experience to analyse the effects of risk on construction operations and sector performance (Ekung et al, 2021a;Ekung, Okonkwo, & Nwosu, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, there are only two articles in infrastructure project literature that define cost drivers (Ekung et al 2021;Wang and Horner 2007). Ekung et al's (2021) definition is more transferable in research due to its general terminology, whereas Wang and Horner's (2007) is more pragmatic, proposing the "mean value theorem" which uses the BoQ to determine cost drivers. Definitions are mainly given by practitioner institutions (Australian Government 2018;DOE 2018;GAO 2020;RICS 2015).…”
Section: Defining Infrastructure Project Cost Driversmentioning
confidence: 99%